The short-term effects of spiral stabilization on human posture correction - Xue Song; Zhe Li; Yang Song; M. Adeel Alam Shah; Xu-Hui Zhang; Chan Li; Campbell Gilmore; Wen-Bin Jiang; Hong-Jin Sui (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background Changes in human posture directly impact the structures of various body parts, often leading to musculoskeletal disorders. While identifying suitable treatments for pain associated with long-term postural abnormalities is important, preventing such conditions is demonstrably a superior solution. Spiral stabilization, known for its practical application, has proven effective in treating low back pain. However, its efficacy in correcting human posture warrants further validation. Methods A total of 71 participants with abnormal body posture, with a mean age of 33.68 ± 6.78 years, were included in this research. The participants underwent spiral stabilization practice for one hour daily for four days. The posture-related angles and deviations from the anterior and lateral views were calculated by the Exbody musculoskeletal analysis system. Results There are statistically significant improvements in most posture-related angles and deviations after the intervention of the spiral stabilization technique compared to before the intervention (P < 0.05). Conclusion The findings of this study suggest that the spiral stabilization technique is a potential intervention for improving human posture. It may become an effective fitness exercise that is widely adopted in daily life to prevent postural abnormalities. Trial registration Registration date is July 10, 2021. The registration number is ChiCTR2100048568.